xdy + (y - x2 y2 ) dx = 0
Solution
"xdy + (y - x^2y^2 ) dx = 0"
Divide through by "dx" as follows
"x{dy\\over dx} + (y - x^2y^2 ){ dx\\over dx} = {0\\over dx}"
We get
"x{dy\\over dx} + (y - x^2y^2 ) =0"
"x{dy\\over dx} + y - x^2y^2 =0"
This is a first-order nonlinear differential equation
Let "u=xy"
Use product rule of differentiation to differentiate "u=xy" with respect to "x"
"u=xy"
"{du\\over dx}=({d\\over dx}(x)).y+x.({d\\over dx}(y))"
"\\implies {du\\over dx}=y+x{dy\\over dx}"
From "{du\\over dx}=y+x{dy\\over dx}" ,We can get expression for "{dy\\over dx}"
"{du\\over dx}=y+x{dy\\over dx}"
"x{dy\\over dx}={du\\over dx}-y"
Now, divide through by "x" to get
"{dy\\over dx}={{du\\over dx}-y \\over x}={{du\\over dx}\\over x}-{y\\over x}"
From "u=xy" , "y={u\\over x}"
"\\therefore {dy\\over dx}={{du\\over dx}\\over x}-{{u\\over x}\\over x} ={{du\\over dx}\\over x}-{u\\over x^2}"
Now, let's substitute "{dy\\over dx}" and "y" to the differential equation
"x{dy\\over dx} + y - x^2y^2 =0"
"x({{du\\over dx}\\over x}-{u\\over x^2})+ {u\\over x} - x^2({u\\over x})^2 =0"
"{{du\\over dx}}-{u\\over x}+ {u\\over x} - x^2.{u^2\\over x^2} =0"
"{{du\\over dx}}- u^2=0"
"\\implies {du\\over dx}=u^2 \\implies {du\\over u^2}=dx"
Take integral on both sides of "{du\\over u^2}=dx"
we have
"\\int{du\\over u^2}=\\int dx \\implies -{1\\over u}=x+C \\implies u=-{1\\over x+C}"
Recall "y={u\\over x} \\implies y={-{1\\over x+C}\\over x}=-{1\\over x+C}\\times{1\\over x}=-{1\\over x(x+C)}"
"\\therefore" the general solution is thus "y=-{1\\over x(x+C)}"
Comments
Leave a comment